KAJIAN LOKASI POTENSIAL PERUMAHAN DAN PERMUKIMAN DI KABUPATEN PESAWARAN DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) - Nadian Maretta; Citra Dewi; Fauzan Murdapa; Eko Rahmadi (Jurnal Geofisika Eksplorasi, 2019)
Pesawaran District, as a new district which was established in 2007, has experienced a rapid growth in population. As the population increases, housing and residential land needs will increase. Therefore, there should be a careful planning in determining the location of housing and settlement development in Pesawaran District. This study aims to: 1) Know the weight for each parameter used in determining the level of potential for a land for the development of housing and residential areas with method AHP 2) Know the potential level of land in Pesawaran District for the development of housing and settlements. The method used is AHP (Analytic Hierarchy Process), while the method by spatial analysis using GIS (Geographic Information System).The results of the study with AHP calculations show that the most dominant parameter is accessibility. The reason is, accessibility will affect the ease of transportation services and affordability of distance. The results of the analysis using GIS resulted in 5 potential locations for the development of residential and residential areas in Pesawaran District which are very potential (13456.50 ha), potential (47941.61 ha), quite potential (47362.11 ha), less extensively potential (16107.09 ha), and no potential (8251.13 ha).